Macular Atrophy Progression and 7-Year Vision Outcomes in Subjects From the ANCHOR, MARINA, and HORIZON Studies: the SEVEN-UP Study - Bhisitkul, Robert B.; Mendes, Thais S.; Rofagha, Soraya; Enanoria, Wayne; Boyer, David S.; Sadda, SriniVas R.; Zhang, Kang (American journal of ophthalmology, 2015)
To assess the incidence and progression of macular atrophy and other key anatomic outcomes over 7 to 8 years in an early cohort of ranibizumab-treated exudative age-related macular degeneration patients. Follow-up analysis of long-term outcomes in a multicenter treatment cohort. Fourteen study sites enrolled 65 previous subjects from the ranibizumab treatment arms of the ANCHOR, MARINA, and HORIZON trials. In a single update visit, clinical assessment and retinal imaging studies were performed, with comparison with each subject’s prior results from the previous trials. Early Treatment Diabetic Retinopathy Study visual acuity was the primary outcome. Secondary outcomes, including area of macular atrophy and selected anatomic factors, were analyzed for associations with long-term vision outcomes. At a mean 7.3 years after ANCHOR or MARINA enrollment, mean visual acuity was 54 letters, study eyes having received a mean 1.6 injections per year since the HORIZON study. Macular atrophy was present in 98% of study eyes, the mean area increasing from 0.83 ± 0.96 mm2 at the ANCHOR or MARINA year 2 exit to 2.22 ± 1.6 mm2 at the SEVEN-UP visit, a growth rate of 0.28 mm2/year. Progression of macular atrophy was associated significantly with visual decline over this 5-year period (P < .001), and final macular atrophy lesion size was related significantly to final vision (P < .001). Other key anatomic outcomes (macular thickening, thinning, or fluid and submacular fibrosis) did not have significant effects on vision outcomes. Seven years after initiation of intensive ranibizumab therapy for exudative age-related macular degeneration, macular atrophy progression and severity were the primary anatomic determinants of visual outcomes.